Democritus’ hypothesis’ of the origins of music - Żerańska-Kominek, Sławomira (Interdisciplinary Studies in Musicology, 2018)
The oldest conception of the origins of music in European culture was formulated by Democritus, who stated that music arose as an imitation of birdsong. This conception was the most serious working hypothesis on the beginnings of music before Darwin. In the musicography of the seventeenth and eighteenth centuries it constituted an alternative to the predominant creationistic theory, paving the way for the scientific positivist approaches which in the nineteenth century led to the eventual depreciation of thinking rooted in religion. In evolutionistically- and scientisticallyoriented comparative musicology the mimetic theory was rejected on the grounds of a lack of scientific evidence of the evolutionary link between birds and man and especially between birdsong and music.The aim of the article is to show that the mimetic theory of the origins of music was a relict of a mythical vision in which birds represented the materialised image of transcendence. The beginnings of music were linked to the voices of birds, which in many cultures symbolised human spirituality—above all spirituality manifest through death. Thus Democritus’ ‘hypothesis’ may be interpreted as a myth in which the ‘song of the beginning’ is identified with mourning